Potential of palm frond waste as a basic material for making porous activated carbon - Novi Yanti; Pharada Kresna; Muhammad Nasir; Rakhmawati Farma; Lilik Tri Hardanto; Rika Taslim; Erman Taer (Indonesian Physics Communication, 2024)
Palm frond waste (Elaeis guineensis Jacq.) has been successfully processed as a raw material in the manufacture of porous activated carbon through the development of tools and methods. Preparation of raw materials, drying, pre-carbonization using an energy-efficient furnace, washing, integrated pyrolysis (N2/H2O), neutralization, and conversion of carbon powder into monolith coins are the general steps for making porous activated carbon. The focus of this research lies in increasing the production of activated carbon from a laboratory scale to an industrial scale through efficiency in all aspects of production. Precarbonization and pyrolysis are important stages in increasing the scale of activated carbon production. Currently, the conversion of biomass waste into carbon is still on a laboratory scale, namely by using an electric oven which is not time efficient, not economical and not energy efficient. Increasing the scale of pre-carbonization is carried out by replacing the use of electric ovens with modified energy-saving furnaces that can increase carbon production up to 74% in a very efficient time. Furthermore, the physical activation stage (pyrolysis) is carried out in a water vapor (H2O) environment and without the addition of chemicals as activating agents, of course it is more economical and environmentally friendly. This scale-up is the main key in the development of porous carbon which has high potential for application as a component in energy storage devices, namely electrodes in supercapacitors. Through these results it is known that the fronds of palm leaves have great potential as a basic material for making sustainable activated carbon to be forwarded to an industrial scale.